Assessment of the High Incidence of COVID-19 in Vaccinated and Unvaccinated Individuals and its Relationship with Several Physical Indicators - T. Ahmed, Shatha; H. Shehab, Zina; MH Al-Shimmary, Sana; H. Jassim, Emad; A. M. Amen, Mena (Al-Nahrain Journal of Science, 2024)
COVID-19 vaccines have shown good efficiency in clinical routs, but some people may be infected after vaccination. The objective of the present study was to review the risk factors for COVID-19 infection after vaccination and to define the characteristics of the disease post-vaccination. her survey was conducted among 451 participants of both sexes, ranging in age from 18 to over 60 years, and also included information about COVID-19 patients, including their weight, blood type, geographic location, symptoms, diagnosis, health risk factors, and duration of infection. In our study, people vaccinated with COVID-19 vaccines (Pfizer, Sinopharm, and AstraZeneca) showed fewer symptoms compared to those who were unvaccinated, with the Pfizer vaccine being particularly effective in reducing symptoms. The degree of persistence of symptoms was reduced. There was an increase in those with chronic conditions, but by less than a month indicating that vaccination may mitigate the severity and duration of symptoms in COVID-19 patients.